2012
DOI: 10.1111/j.1349-7006.2012.02268.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitization effect of poly(ADP‐ribose) polymerase inhibition in cells exposed to low and high liner energy transfer radiation

Abstract: Poly(ADP-ribose) polymerase (PARP)-1 promotes base excision repair and DNA strand break repair. Inhibitors of PARP enhance the cytotoxic effects of c-irradiation and X-irradiation. We investigated the impact of PARP inhibition on the responses to c-irradiation (low liner energy transfer [LET] radiation) and carbon-ion irradiation (high LET radiation) in the human pancreatic cancer cell line MIA PaCa-2. Cell survival was assessed by colony formation assay after combination treatment with the PARP inhibitor AZD2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 21 publications
2
50
0
Order By: Relevance
“…As high LET radiation produces complex types of DNA damage, which are a mixture of single strand break and DSB, PARP may be a promising therapeutic target (21)(22)(23). The results of the present study appear to be in accordance with the PARP inhibitor-induced sensitization with high LET radiation (24), and indicate PARP inhibition may be a potential target for heavy ion radiation therapy.…”
Section: Discussionsupporting
confidence: 77%
“…As high LET radiation produces complex types of DNA damage, which are a mixture of single strand break and DSB, PARP may be a promising therapeutic target (21)(22)(23). The results of the present study appear to be in accordance with the PARP inhibitor-induced sensitization with high LET radiation (24), and indicate PARP inhibition may be a potential target for heavy ion radiation therapy.…”
Section: Discussionsupporting
confidence: 77%
“…PARP1 promotes BER and single-strand break repair (SSBR), and PARP inhibitors, by blocking BER, lead to an increase of collapsed replication forks generating DSBs [262]. Radiosensitization of MiaPaCa-2 cells with olaparib (AZD2281) alone has been reported [263]. Similarly, the same group of researchers have also shown that the combined inhibition of Wee1 tyrosine kinase using a small molecule inhibitor AZD1775 and PARP1 inhibitor olaparib radiosensitizes AsPC-1 and MiaPaCa-2 PC cells significantly.…”
Section: Promising Molecular Targeting Agents As Radiosensitizers mentioning
confidence: 99%
“…Focused-beam X-ray radiation produces localized double-stranded DNA breaks and thus would be expected to render cells more sensitive to PARP inhibition (19, 20). Olaparib has been shown to enhance the effect of radiation in both BRCA2-proficient and deficient prostate cancer cells (21).…”
Section: Introductionmentioning
confidence: 99%